Influence of Chemical Inhomogeneities on Local Phase Stabilities and Material Properties in Cast Martensitic Stainless Steel. Issue 5 (25th November 2019) - van gen Hassend, Frederic; Weber, Sebastian
Abstract : Cr–Mo‐alloyed cast martensitic stainless steels are suitable tool materials for a wide field of applications. Local inhomogeneities in the chemical composition, however, affect their local and global properties such as the hardenability and the corrosion resistance. Herein, the influence of microsegregations on phase stabilities and properties is investigated by means of property distribution maps (PDM) which are determined via thermodynamic and empirical calculations based on measured local chemical composition data. The results show that the enrichment of Cr and Mo in interdendritic regions benefits the local corrosion resistance but increases the solvus temperature of M23 C6 carbides from 1040 to 1150 °C and depresses the martensite start temperature (Ms ) to temperatures below 50 °C locally. As predicted from the PDM, high‐temperature austenitization at 1150 °C combined with a cryogenic treatment at −80 °C ensures a martensitic microstructure with relatively high hardness (592 ± 12 HV10) and significantly higher critical pitting potential compared with specimens austenitizized at 1050 °C, which proves PDM to be a powerful tool for the optimization of heat treatment parameters. However, local transformation of austenite into δ‐ferrite during austenitization at 1150 °C must be considered. Abstract : Herein, a quantitative prediction of local phase stabilities and properties such as hardenability and pitting corrosion resistance based on calculated property distribution maps for the solvus temperature of carbides of M23 C6 type, the martensite start temperature (Ms), and the pitting resistant equivalent number (PREN) is given.